PERENCANAAN NAMA MEREK (BRAND NAME) MANISAN MANGGA INDRAMAYU KERING BERBASIS NILAI PELANGGAN (Studi Kasus : Produk Inovasi Balai Besar Pascapanen, Bogor, Jawa Barat) - Fitri Dana Kristiana; . Maulidian; . Arman (Universitas Trilogi, 2021)
A study on brand name planning candied dried mango indramayu based on customer value. The purpose of this study is to identify the customer profile, design a value proposition and plan the brand name of candied dried mango products. The results showed that the needs of the millennial generation were choosing the place, buying and bringing the product home; looking for healthy snacks; have a healthy and ideal body; avoid foods that are too sweet and too sour. They also have a problem (pains) when consuming dried mango candies which are pieces of mango are too thin, the taste is too sour, the sugar layer is too much, and there is a bitter taste when eaten. Besides the desire (gains) millennial generation including the taste is not too sour and sweet, do not use harmful preservatives, use quality mangoes, affordable prices, attractive product packaging and easy to carry everywhere. Subsequently,